52.7k views
1 vote
Given the following functions f(x) and g(x), solve (f ⋅ g)(3) and select the correct answer below: f(x) = 4x^2 + 12 g(x) = x − 1 47 −47 96 −96

User Kolypto
by
7.0k points

1 Answer

7 votes
For this case we have the following functions:
f (x) = 4x ^ 2 + 12
g (x) = x - 1
Multiplying the functions we have:
(f ⋅ g) (x) = f (x) * g (x)
(f ⋅ g) (x) = (4x ^ 2 + 12) * (x - 1)
Evaluating for x = 3 we have:
(f ⋅ g) (3) = (4 (3) ^ 2 + 12) * (3 - 1)
(f ⋅ g) (3) = (4 (9) + 12) * (2)
(f ⋅ g) (3) = (36 + 12) * (2)
(f ⋅ g) (3) = (48) * (2)
(f ⋅ g) (3) = 96
Answer:
(f ⋅ g) (3) = 96
User Pini Reznik
by
7.2k points